Rentabilidad de los bancos comerciales en Portugal y Espa\~na: Un modelo de análisis de datos de pane; Profitability of commercial banks in Portugal and Spain: A panel data analysis model - Marco Amara (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– The Portuguese and Spanish banking system, in the framework of the economic and financial crisis suffered a significant reduction in the profitability of its banking business. Taking into consideration the problem of profitability in the banking sector at a global level, some studies have been increasingly highlighted both in academia and in the financial market. Thus, this paper aims to analyze the determinants of banking profitability of banks operating in two different financial systems, Portugal and Spain, for the periods from 2014 to 2019. To obtain the results, we used a panel data analysis model that combines cross-section (banks) and time-series (years) data, obtaining a strongly balanced panel. Multiple linear regression models were then used and it was possible to identify credit risk, solvency and operational efficiency as the main factors explaining bank profitability. Finally, the results show that the high credit risk and operational efficiency indicators of these banks have a negative significant influence on their profitability. In turn, more robust solvency indicators have a positive significant dominant on bank s performance.
Keywords: G21; N20; 330; Performance; banks; profitability; financial system; panel data